Comparative Assessment Model of Natural Resources Mix in The European Context - Mihaela Adina MATEESCU; Mihai SabinMUSCALU; Elena Manuela ISTOC; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2025)
This paper presents an analysis of primary energy production from renewable and non-renewable sources. It determines which energy from non-renewable sources is replaced by energy from renewable sources for each EU member country considered. Additionally, the present paper also shows us a cluster analysis of EU member countries according to the share of renewable sources in total electricity production from renewable sources and biofuels. All data used for the study were taken from the EUROSTAT and IRENA 2024 databases. The countries considered are: Romania, Bulgaria, Italy, Greece, Croatia, Poland, Hungary, Slovakia, Spain, Czech Republic, Belgium, Portugal, France, Germany, Slovenia, Lithuania, Estonia, Latvia, Austria, Denmark, Netherlands and Sweden.
Keywords: primary energy production; renewable and non-renewable resources; cluster analysis; model